Loss of CD26 protease activity in recipient mice during hematopoietic stem cell transplantation results in improved transplant efficiency. Issue 4 (6th August 2012) - Yoo, Eunsun; Paganessi, Laura A.; Alikhan, Wasfia A.; Paganessi, Elizabeth A.; Hughes, Frank; Fung, Henry C.; Rich, Elizabeth; Seong, Chu Myong; Christopherson 2nd, Kent W.
<x xml:space="preserve">Abstract</x> BACKGROUND: A firm understanding of the biology of hematopoietic stem and progenitor cell (HSC/HPC) trafficking is critical to improve transplant efficiency and immune reconstitution during hematopoietic stem cell transplantation (HSCT). Our earlier findings suggested that suppression of CD26 (dipeptidyl peptidase IV) proteolytic activity in the donor cell population can be utilized as a method for increasing transplant efficiency. However, factors in the recipient should not be overlooked, given the potential for the bone marrow (BM) microenvironment to regulate HSCT. STUDY DESIGN AND METHODS: We first evaluated CD26 expression and then investigated the effects of the CD26 inhibitor diprotin A and the absence of CD26 (CD26−/−) in recipient mice on HSC/HPC homing and engraftment using an in vivo congenic mouse model of HSCT. RESULTS: A significant increase in donor cell engraftment into the peripheral blood (PB), and to a lesser extent homing into the BM, was observed in CD26−/− mice or CD26 inhibitor–treated mice. Increased PB engraftment of CD26−/− mice was significant at 3 and 6 months, but not 1 month, after transplant. It was noted that the increased homing was statistically greater with donor cell manipulation (CD26−/− donor cells) than with recipient manipulation (CD26−/− recipient mice). Conversely, donor and recipient manipulation both worked well to increase PB engraftment at 6 months. CONCLUSION: These results provide preclinical evidence of CD26, in the HSCT recipient, as a major regulator of HSC/HPC engraftment with minor effects on HSC/HPC homing and suggest the potential use of CD26 inhibitors in HSCT patients to improve transplant efficiency.